(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2025)
The intention of present study is to ascertain the relationship between the serum inflammatory markers in patients with RHD (rheumatic heart disease), which includes Interleukin-6, C-reactive protein, NT-proBNP and troponin I (TnI). 108 RHD patients were assessed, who visited Dhanya Cardiac Centre for regular check-up. The patient's concern regarding the use of their samples for this study has been acknowledged. Quantitative analysis of biomarkers such as IL-6, CRP, NT-pro BNP, Troponin I was performed. The findings revealed a significant upsurge in IL-6 and CRP levels in the preoperative patients as compared with postoperative patients. Alternatively, NT-pro BNP and Troponin I levels didn’t show significant upsurge in pre-operative patients, while these markers were elevated in the initial stage of post-operative period. Our findings provide an insight on numerous factors and biomolecules might assist as potential markers related with the progression of rheumatic fever (RF) and RHD. Moreover, a follow-up study including a larger population is essential, as it could assist clinicians in predicting any predisposition to RHD.